Conservation refugees and environmental dispossession in 21st century critical Geography - Scott William Hoefle (Boletín de la Asociación de Geógrafos Españoles)
This study explores the relevance of the concepts of conservation refugees and environmental dispossession for steering a middle course between unjust bio-centric conservation and anti-environmentalism of extreme right “populism”. Historical geographers have recently taken up these concepts from contemporary Environmental History, and when with allied to the concepts of environmental ethics from Radical Ecology and Environmental Studies and nature enclosures from Political Ecology, a novel critique is produced of the role of full conservation units in debates surrounding global climate change. This kind of nature reserve is steeped in bio-centric environmental ethics which distill nature and dispossess native peoples and poor peasants. The latter are considered to be anthropic agents who are criminalized, removed and turned into conservation refugees in order to cleanse the landscape of (poor rural) human presence. Drawing on research undertaken on nature enclosures in three threatened biomes of Brazil, hybrid views of society-nature and actor-network assembly from Relational Geography are used to interpret specific cases involving successful resistance to environmental dispossession in which local people forced a change in mentality of nature reserve administrators, turned foe into ally and built socially inclusive conservation strategies.